The Influence Of Organizational Commitment On Employee Job Satisfaction Through Servant Leadership On The It&B Campus - Agus Susanto (International Journal of Economics, Business and Innovation Research, 2024)
The objective of this study is to investigate the correlation between organizational commitment, servant leadership, and employee job satisfaction in the IT&B campus setting. Organizational commitment is often seen as a vital factor that influences employee performance and loyalty. Similarly, servant leadership is seen as a leadership style that promotes employee service and strengthens the bond between leaders and followers. This study use a quantitative methodology to provide a detailed and explanatory analysis. To gather data from individuals employed in different departments of the IT&B campus, we will employ a survey methodology and administer a questionnaire. The population for this study comprises all 51 people currently employed at the IT&B Campus. The sampling strategy utilizes a saturated sample approach, where the whole population is used as the study sample. We do data analysis using Smart PLS through several sources. The research seeks to get a comprehensive knowledge of the elements that impact employee work satisfaction in educational institutions such as IT&B campuses. It also intends to give practical advice to campus management on how to improve employee well-being and performance. We anticipate that the research's findings will establish a basis for developing more efficient management policies and practices within the IT&B campus environment and comparable institutions.